Association between benzodiazepine receptor agonist use and mortality in patients hospitalised for COVID-19: a multicentre observational study. (30th March 2022) - Hoertel, N.; Sánchez-Rico, M.; Gulbins, E.; Kornhuber, J.; Vernet, R.; Beeker, N.; Neuraz, A.; Blanco, C.; Olfson, M.; Airagnes, G.; Lemogne, C.; Alvarado, J. M.; et al.
Abstract: Aims: To examine the association between benzodiazepine receptor agonist (BZRA) use and mortality in patients hospitalised for coronavirus disease 2019 (COVID-19). Methods: A multicentre observational study was performed at Greater Paris University hospitals. The sample involved 14 381 patients hospitalised for COVID-19. A total of 686 (4.8%) inpatients received a BZRA at hospital admission at a mean daily diazepam-equivalent dose of 19.7 mg (standard deviation (s.d. ) = 25.4). The study baseline was the date of admission, and the primary endpoint was death. We compared this endpoint between patients who received BZRAs and those who did not in time-to-event analyses adjusted for sociodemographic characteristics, medical comorbidities and other medications. The primary analysis was a Cox regression model with inverse probability weighting (IPW). Results: Over a mean follow-up of 14.5 days (s.d. = 18.1), the primary endpoint occurred in 186 patients (27.1%) who received BZRAs and in 1134 patients (8.3%) who did not. There was a significant association between BZRA use and increased mortality both in the crude analysis (hazard ratio (HR) = 3.20; 95% confidence interval (CI) = 2.74–3.74; p < 0.01) and in the IPW analysis (HR = 1.61; 95% CI = 1.31–1.98, p < 0.01), with a significant dose-dependent relationship (HR = 1.55; 95% CI = 1.08–2.22; p = 0.02). This association remained significant in sensitivity analyses. Exploratory analyses indicate that most BZRAs may be associated with an increased mortality among patients hospitalised for COVID-19, except for diazepam, which may be associated with a reduced mortality compared with any other BZRA treatment. Conclusions: BZRA use may be associated with an increased mortality among patients hospitalised for COVID-19, suggesting the potential benefit of decreasing dose or tapering off gradually these medications when possible.